Robust quasi-LPV model reference FTC of a quadrotor UAV subject to actuator faults - Rotondo, Damiano; Nejjari, Fatiha; Puig, Vicenç (Zielona Góra: Uniwersytet Zielonogórski)
A solution for fault tolerant control (FTC) of a quadrotor unmanned aerial vehicle (UAV) is proposed. It relies on model reference-based control, where a reference model generates the desired trajectory. Depending on the type of reference model used for generating the reference trajectory, and on the assumptions about the availability and uncertainty of fault estimation, different error models are obtained. These error models are suitable for "passive FTC", "active FTC" and "hybrid FTC", the latter being able to merge the benefits of active and passive FTC while reducing their respective drawbacks.
Keywords: linear parameter varying systems; fault tolerant control; quadrotor; model reference-based control; linear matrix inequalities